Detection of Papillomavirus Gene Expression Patterns in Tissue Sections. Issue 1 (6th May 2016) - Griffin, Heather; Doorbar, John
Abstract: Molecular events during the papillomavirus life cycle can be mapped in infected tissue biopsies using antibodies to viral and cellular gene products, or by in situ hybridization approaches that detect viral DNA or viral transcription products. For proteins, ease of immunodetection depends on antibody specificity and antigen availability. Epitopes in formalin‐fixed paraffin‐embedded (FFPE) samples are often masked by crosslinking and must be exposed for immunodetection. RNA in FFPE material is often degraded, and such tissue must be handled carefully to optimize detection. Viral proteins and viral genomic DNA are both well preserved in routinely processed FFPE samples, with sensitive detection methodologies allowing the simultaneous detection of multiple markers. The combined visualization of nucleic acid and (viral) protein targets, when coupled with image analysis approaches that allow correlation with standard pathology diagnosis, have allowed us to understand the molecular changes required for normal HPV life‐cycle organization as well as deregulation during cancer progression. © 2016 by John Wiley & Sons, Inc.